Government Role in Agricultural Management as Agrarian Resource - Herlindah (Hang Tuah Law Journal, 2017)
Agriculture is a one of land resources called agrarian which brings strategic functions and roles for Indonesia as agrarian country. It is identified as being strategic due to a great number of Indonesian people who rely their lives on agricultural sector. Thus, farms do not only have economic value but also social value, and even religious one. Besides, farms are also subjected for agricultural investment activities involving hugecapital companies through which a large-scale extensification of farms will increase over time. This paper focused on the state control over agrarian resources. Starting from farms as agrarian resources, the governance rights of land by a country is based on both UUPA and the exegesis of Constitutional Court. Findings showed that there were 4 (four) models of The state control over agrarian resources based on Article 2 UUPA. However, as Constitutional Court verdict Number 002/PUU-I/2003 testing toward the Law Number 22, 2001 on oil and gas toward the Constitution 1945 was established, the state control over farms could be broadly defined as public rights for all people of Indonesia over its agrarian resources.